Brazilian Infants’ Sensitivity To Prosodic Cues Of Intonational Phrase Boundaries On Infant Directed Speech - Silva, Ícaro Oliveira (2014)
This study investigates whether Brazilian infants are able to analyze acoustic properties of linguistic input in order to perceive word and sentence boundaries (cf. NESPOR; VOGEL, 1986; PIERREHUMBERT, 1980; LADD, 2008). The focus of the study is on infant sensitivity to prosodic cues of Intonational Phrase (I) boundaries on Infant Directed Speech (IDS) stimuli; and on their ability to use cues in word discrimination tasks. Two activities were carried out: the first activity analyzed IDS utterances extracted from Brazilian mother-baby social interaction in order to identify prosodic properties of I-boundaries; the Second activity, an experimental one, tested whether 13-month Brazilian infants are sensitive to these properties and use them to discriminate a word with which they were familiar. The results suggest that prosodic I-boundary cues were perceived by babies and facilitated word segmentation. We argue that acoustic information presented in prosodic constituents boundaries are amplified on IDS stimuli and may facilitate language acquisition bootstrapping (cf. Prosodic Bootstrapping Hypothesis: MORGAN; DEMUTH, 1996; CHRISTOPHE et al., 1997).